Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3920/jiff2014.0022
|View full text |Cite
|
Sign up to set email alerts
|

Diseases in insects produced for food and feed

Abstract: Increased production of insects on a large scale for food and feed will likely lead to many novel challenges, including problems with diseases. We provide an overview of important groups of insect pathogens, which can cause disease in insects produced for food and feed. Main characteristics of each pathogen group (viruses, bacteria, fungi, protists and nematodes) are described and illustrated, with a selection of examples from the most commonly produced insect species for food and feed. Honeybee and silkworm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 72 publications
0
117
0
2
Order By: Relevance
“…A recent scientific opinion of the EFSA Scientific Committee (EFSA ) reported that antimicrobials can be used during insect rearing as an emergency treatment for diseases caused by bacteria, fungi or microsporidia (Tarapoulouzi and others ; Eilenberg and others ). Hence, the occurrence of AR genes in edible insects could be a direct consequence of these practices.…”
Section: Resultsmentioning
confidence: 99%
“…A recent scientific opinion of the EFSA Scientific Committee (EFSA ) reported that antimicrobials can be used during insect rearing as an emergency treatment for diseases caused by bacteria, fungi or microsporidia (Tarapoulouzi and others ; Eilenberg and others ). Hence, the occurrence of AR genes in edible insects could be a direct consequence of these practices.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include microsporidia, nematodes, apicomplexa parasites and miscellaneous other single-cell organisms which may be present in insect mass cultures, in particular when cultured under insufficient hygienic conditions. This problem has not yet been sufficiently covered in the literature [20]. The housefly M. domestica is a nutritional competitor in sparsely populated food containers, but more importantly, the flies may be vectors for pathogens.…”
Section: Sustainable Production Of Proteins and Lipids From Mass Cultmentioning
confidence: 99%
“…Insects have a specific plethora of viral pathogens that are considered safe for humans and are even, in some cases, approved as biocontrol agents in agriculture. Conversely, human viruses taxonomically related to insect ones are known to be unable to replicate in insects and would therefore not pose health concerns (Eilenberg, Vlak, Nielsen‐Leroux, Cappellozza, & Jensen, ). However, studies are needed for particular groups of viruses, since the arthropod‐borne viruses (arboviruses) are able to cause human diseases (such as dengue, West Nile disease, rift valley fever, hemorrhagic fever, chikungunya) and are able to replicate in their vectors (King, Adamse, Carstens, & Lefkowitz, ).…”
Section: Microbiological Hazardsmentioning
confidence: 99%